Tender is the night - Fitzgerald, F. Scott (Francis Scott), 1896-1940. (London : Wordsworth, 1995)
The tragic and haunting story of Dick Diver, a young psychiatrist whose career is thwarted and his genius numbed through marriage to the exquisite and wealthy Nicole Warren.
Young Adult
Keywords: Psychiatrists -- Fiction; Wealth -- Moral and ethical aspects -- Fiction; Psychiatrists -- Fiction; Wealth -- Fiction; Riviera (France) -- Fiction; Riviera (France) -- Fiction